EGOCENTRISM AS A FACTOR OF THE MANAGERIAL COMPETENCE DEVELOPMENT - D. Polezhaeva, Olga; N. Sofina, Vera; P Gabova, Maria (Revista Gênero e Interdisciplinaridade, 2020)
the article is devoted to the study of egocentrism. The topicality of this problem is stipulated by the fact that the results of the research on human motives to determine one’s ability or inability to act for the benefit of others and sacrifice one’s own interests for the sake of achieving a common high goal are in high demand nowadays among specialists engaged in teambuilding at work, sport events and so on. The purpose of the article is to study reasons for the egoistic and altruistic behavior of a person, as well as identify tendencies for a particular behavior with the help of modern technologies. The leading method to investigate this problem is cybertraining, the application of which makes it possible to identify the motivation of an individual to achieve common results in teamwork, as well as the influence of internal and external factors on this motivation. The conducted study revealed a close relation between the person’s inner attitude towards cooperation and high success rates of an individual. It was also found that the method of cybertraining allows to reveal with a high degree of accuracy the ability and inability of a participant to perform in a joint activity. The results of the study can be practically useful in business coaching, training cosmonauts and employees from other areas where successful teamwork plays a key role in achieving the organization’s goals.